Evaluating influence of technology readiness factors on the Saudi cement companies market and financial based performance. Issue 2 (25th May 2018) - Alsultanny, Yas; AlZuhair, Sara
Abstract : Purpose: The purpose of this paper is to assess the technology readiness factors and their influence on the market- and financial-based performance of Saudi cement companies from managers' perspective. Design/methodology/approach: The tool of the study is a questionnaire, which is developed to measure technology readiness from the cement companies' managers' perspectives; it has six dimensions with 42 statements. Findings: The findings showed managers' degree of agreement on the variables; technology readiness contributors (optimism and innovativeness) were set in the agree category, and the inhibitors (discomfort and insecurity) were set in the neutral category. The results also showed no statistically significant influence from the contributors on market-based performance and moderate influence from the inhibitors on market-based performance. Research limitations/implications: The research was limited to the Saudi cement companies. Originality/value: This is the first paper to evaluate the Saudi cement companies for technology readiness from perspective of the companies' managers.